Togo : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2014)
This Poverty Reduction Strategy Paper highlights that Togo's Strategy for Boosting Growth and Promoting Employment offers a medium-term development framework for implementing the Government's General Policy Statement, the Millennium Development Goals, and the Government's vision for making Togo an emerging economy in 15 to 20 years, as well as making it a country that respects human rights and promotes the rule of law. The return of political stability and peace to the country created a favorable environment for better governance, resumption of international assistance, and significant reduction in exterior public debt. The Government's medium-term economic policy for 2013-2017 will essentially be used to build and consolidate the foundations for Togo's future economic emergence. The focus will be on new priorities: boosting growth; employment and inclusion; strengthening governance; and reducing regional disparities and promoting grassroots development. Designing a national land-use plan will territorialize development by creating a more balanced national economic space. The new land-use scheme will be based on dynamic, competitive, regional economies in which the urbanization of regional capitals and secondary towns is sufficiently controlled to allow true development hubs to emerge.